Exact Solutions of the Space Time Fractional Symmetric Regularized Long Wave Equation Using Different Methods - Özkan Güner; Dursun Eser (Advances in Mathematical Physics)
We apply the functional variable method, exp-function method, and (G′/G)-expansion method to establish the exact solutions of the nonlinear fractional partial differential equation (NLFPDE) in the sense of the modified Riemann-Liouville derivative. As a result, some new exact solutions for them are obtained. The results show that these methods are very effective and powerful mathematical tools for solving nonlinear fractional equations arising in mathematical physics. As a result, these methods can also be applied to other nonlinear fractional differential equations.